Exploring the effects of genotypical and phenotypical variations in bitter taste sensitivity on perception, liking and intake of brassica vegetables in the UK. (June 2016) - Shen, Yuchi; Kennedy, Orla B.; Methven, Lisa
Highlights: TAS2R38 PAV/PAV and high fungiform papillae density lead to high PROP sensitivity. Brassica vegetables perceived as more bitter than non-brassica vegetables. PAV/PAV subjects perceived significantly stronger bitter intensity from brassica. Compared to other TAS2R38 groups, AVI/AVI subjects liked brassica vegetables most. Gender had a substantial influence on vegetable preference and intake. Abstract: Brassicaceous vegetables (BV) have chemoprotective effects and yet consumption of BV in the UK is low. Previous studies suggest perception, liking and intake of BV are influenced by bitter taste sensitivity which this study further explores. Phenotypical taste sensitivity of 136 subjects was classified using propythiouracil (PROP) and sodium chloride and fungiform papillae density (FPD) was measured from tongue images. Polymorphisms of TAS2R38 and gustin (CA6) genes were analysed. Liking and bitterness of four raw vegetables (two BV (broccoli and white cabbage) and two non-BV (spinach and courgette)), as well as habitual consumption, were evaluated. There was a significant association between TAS2R38 genotype and PROP taster status ( p < 0.0001) and between FPD and PROP taster status ( p = 0.029). Individuals with greater sensitivity for PROP predominantly had TAS2R38 PAV/PAV genotype and greater FPD. BV were perceived as more bitter than non-BV ( p < 0.0001) with PAV/PAV subjects perceiving significantly stronger bitter intensity. There was a significant difference in liking for the four vegetables ( p = 0.002), and between consumers of different TAS2R38 genotype ( p = 0.0024). Individuals with TAS2R38 AVI/AVI genotype liked BV more. Regarding intake, both PAV/PAV and AVI/AVI individuals consumed more total vegetables and BV than PAV/AVI. Although PROP nontasters tended to consume more vegetables and BV than the other two phenotype groups, liking and vegetable intake were not significantly affected by taste phenotype. Although there was not a significant effect of CA6 genotype on bitterness ratings, there was a significant interaction between CA6 and TAS2R38, and in addition CA6 genotype was significantly associated with BV intake. However, these effects require validation as the proportions of the population with the CA6 G/G genotype was extremely small (7%). Our results confirmed that bitter taste perception in vegetables was influenced by both genotype and phenotype of bitter taste sensitivity. Moreover, our findings demonstrated that neither genotype nor phenotype of taste sensitivity alone accurately predict vegetable liking and intake as demographic factors were found to have a substantial influence.